Patterns of colour inheritance from crossbreeding between Red hybrid tilapia (Oreochromis sp.) and GIFT tilapia (Oreochromis niloticus) - Nwachi, O. F.; Esa, Y. B.; Christianus, A.; Rahim, A. A.; Kamarudin, M. S. (Triveni Enterprises, 2020)
Aim: Methodology: Results: Interpretation: Key words: To examine the pattern of colour inheritances from crossbreeding between Red hybrid tilapia (Oreochromis sp.) and GIFT tilapia (Oreochromis niloticus). A total number of 60 broodstock of 30 each of GIFT and Red hybrid tilapia were selected to produce the first filial generation (F ) and its 1 reciprocal nF . Pairing of female to male were done in the ratio of 3:1. The same breeding scheme were used to produce the second filial generation (F ) 1 2 and its reciprocal nBcF1. Crossbreeding between Red hybrid tilapia male and GIFT female (F ) produced phenotypic colours ranging from red (64.61%), wild type 1 (11.54%), red with blotches (4.96%) and mixed red-wild type (18.87%). The reciprocal cross between GIFT male and Red hybrid tilapia female (nF1) produced phenotypic colours ranging from red (19.65%), wild type (64.62%), red with dark blotches (4.03%) and mixed red-wild type (11.46%). The second filial (F ) generation 2 produced phenotypes comprising of 61.17% wild type, 14.37% red with dark blotches, 20.04% mix red-wild type and 4.40% red type. The backcross (BcF ) produced 10.57 %, faded wild type 22.76 %, red with 1 dark blotches, 28.41 %, red with dark posterior and 60.46 % red phenotype while the reciprocal (nBcF ) produced 52.89% faded wild 1 type, 15.11% red with dark blotches, 6.83% mix red-wild type and 25.15% red phenotype. Manifestation of intermediate and mixed colour phenotypes in F hybrids and deviation from a simple dominant 2 inheritance might indicate an incomplete dominant inheritance, colour determination in tilapia in this study might be located or linked with the male Y-chromosome due to the fact that more reddish coloured fish were produced when Red hybrid tilapia was selected as the parent.